Genetic population structure of penaeid prawns Penaeus monodon Fabricius 1798, Fenneropenaeus indicus H. Milne Edwards 1837 and Metapenaeus monoceros Fabricius 1798 in the Malindi–Ungwana Bay, Kenya - Mkare, Thomas Kalama (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.